2005
DOI: 10.4028/www.scientific.net/amr.6-8.195
|View full text |Cite
|
Sign up to set email alerts
|

Computing Welding Distortion: Comparison of Different Industrially Applicable Methods

Abstract: Abstract. Welding distortion is one of the major concerns of the industrial joining practice. In order to obtain optimal welding parameters many experiments have to be carried out. Numerical simulation enables a virtual examination of the welding distortion without performing expensive experiments. In this contribution some industrially applicable methods of weld modeling are discussed. They enable the fast distortion assessment in the pre-development stage. The application of these methods on a complex automo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…The most of modeling methods tend to be very strongly focused on individual aspects of the welding simulation and are often not considered as part of a holistic system. Especially, in the case of manufacturing process chains, partial models should be investigated as an element of a wider simulation system by preserving efficiency and quality as far as possible [9]. The various influencing phenomena are hierarchized in different modeling levels or sub-systems within the simulation depending on the level of detail of the integrated simulation system.…”
Section: Background and Motivationmentioning
confidence: 99%
“…The most of modeling methods tend to be very strongly focused on individual aspects of the welding simulation and are often not considered as part of a holistic system. Especially, in the case of manufacturing process chains, partial models should be investigated as an element of a wider simulation system by preserving efficiency and quality as far as possible [9]. The various influencing phenomena are hierarchized in different modeling levels or sub-systems within the simulation depending on the level of detail of the integrated simulation system.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Various investigations have been performed in order to trace the development of welding deformations by means of numerical simulation [11][12][13][14]. Sensitivity studies [15][16][17] demonstrate the possibilities and limits of numerical models. This is an important issue, before simulation results can be employed as a reliable basis for the adjustment of process parameters.…”
Section: Welding Simulation In Research Production Planning and Devementioning
confidence: 99%
“…Detailed electro-thermo-mechanical-metallurgical 3D simulations and extensive temperature-dependent material data are required to accurately describe how the residual stresses from previous manufacturing steps evolve during welding. Tikhomirov et al (2005) presented simplified mechanical approaches that may be applicable to evaluate the distortion tendencies qualitatively, but not quantitatively. However, since no reasonably simple simulation method was found that quantitatively predicts the distortion and residual stresses, these effects are neglected in this work.…”
Section: Weldingmentioning
confidence: 99%